Expansão da Educação a distância no Brasil a partir dos anos 1990: o caso da universidade do Tocantins - MAIA, Maria Zoreide Britto (2011)
The present thesis, which is linked to the Research Area State and Educational Politics of the Graduation Program in Education of The Federal University of Goiás, analyzes the process of expansion of higher education in Brazil through distance education (EaD), during Fernando Henrique Cardoso s (1995-2002) and Luiz Inácio Lula da Silva s (2003-2010) administrations, aiming at comprehending, especially, the case of The University of Tocantins (Unitins), which in the 2000s put into work a set of actions and strategies which gave rise to an accelerated process of expansion of distance undergraduate and post-graduation programs. This research, based on the analysis of programs, projects and federal governmental actions, clearly shows that the Brazilian state has been rapidly institutionalizing and expanding distance education. It becomes evident, in this process, that the politics established by the Bureau of Distance Education/MEC, co-substantiate meaningful changes in the conceptions of distance education, access democratization, regulation, evaluation, supervision and vacancy offer quality. Taking the above into consideration, especially the actions implemented between 1995 and 2010, we opted for undertaking the Unitins case study, since that institution turned out to be an example case of the rapid expansion of undergraduate programs by means of distance education. The study analyzed the complex and dynamic re-structuring processes that university went through, considering its academic and institutional background, especially during three moments: its registration to act as a distance education institution in 2004, its rapid expansion which allowed it to enroll over one hundred thousand students and its unregistration effectuated by MEC in 2009. This investigation also tried to understand the interdependence and inter-relation of Unitins with the educational politics, mainly in terms of higher education, in the context of its re-structure and the State s adjustments in light of the productive transformations of a globalized capitalism. In order to understand that process, it was necessary to analyze studies about politics and higher education regulation in Brazil (ADRIÃO, PERONI, 2005; BITTAR, OLIVEIRA e MOROSINI, 2008; CUNHA, 2003; LIMA, 2007a; MINTO, 2006; NEVES, 2004; OTRANTO, 2005; SGUISSARDI, 2000; SILVA JR, 2002; SIQUEIRA, NEVES, 2006, among others) besides critical studies about distance education (BARROSO, 2005; BELLONI, 2002, 2003; DOURADO, 2002, 2008; FRAGALE FILHO, 2003; JARDILINO e BRZEZINSKI, 2008; LITTO, FORMIGA, 2009; LOBO NETO, 2000; MOORE, KEARSLEY, 2007; OLIVEIRA, 2008; PRADO, ROSA, 2008; SEGENREICH, 2006b). Apart from that, documents produced by the Brazilian and Tocantins governments, thesis and dissertations published by CAPES, scientific articles published by SCIELO, local journals and publications found at Unitins website, besides interviews related to the Unitins case, were examined. The research shows that, in the context of higher education re-structure, the federal government elected distance education as one of the mechanisms to promote the expansion of that education level, both for the formation of teachers as well as to increase registrations at higher education institutions, giving emphasis to the importance of vacancy offer democratization. However, the expansion of higher education by means of distance education, took place rapidly and disorderly, as evidenced by the Unitins case, which forced MEC itself to unregister that institution in 2009, since it presented various irregularities regarding vacancy offer. Therefore, this investigation points out that it is necessary to develop better evaluation procedures and to regulate and supervise distance education institutions and programs, with the purpose of securing acceptable standards of academic quality of new distance undergraduate and graduate programs.